Suicidal Ideation and Insomnia in Bipolar Disorders: Idéation suicidaire et insomnie dans les troubles bipolaires. (November 2020) - Bertrand, Lia; Bourguignon, Clément; Beaulieu, Serge; Storch, Kai-Florian; Linnaranta, Outi
Objective: Bipolar disorder (BD) confers elevated suicide risk and associates with misaligned circadian rhythm. Real-time monitoring of objectively measured sleep is a novel approach to detect and prevent suicidal behavior. We aimed at understanding associations between subjective insomnia and actigraphy data with severity of suicidal ideation in BDs. Methods: This prospective cohort study comprised 76 outpatients with a BD aged 18 to 65 inclusively. Main measures included 10 consecutive days of wrist actigraphy; the Athens Insomnia Scale (AIS); the Montgomery–Åsberg Depression Rating Scale (MADRS); the Quick Inventory of Depressive Symptoms-16, self-rating (QIDS-SR-16); and the Columbia Suicide Severity Rating Scale. Diagnoses, medications, and suicide attempts were obtained from chart review. Results: Suicidal ideation correlated moderately with subjective insomnia (AIS with QIDS-SR-16 item 12 ρ =0.26, P = 0.03; MADRS item 10 ρ = 0.33, P = 0.003). Graphical sleep patterns showed that suicidal patients were enriched among the most fragmented sleep patterns, and this was confirmed by correlations of suicidal ideation with actigraphy data at 2 visits. Patients with lifetime suicide attempts ( n = 8) had more varied objective sleep (a higher standard deviation of center of daily inactivity [0.64 vs. 0.26, P = 0.01], consolidation of daily inactivity [0.18 vs. 0.10, P = <0.001], sleep offset [3.02 hours vs. 1.90 hours, P = <0.001], and total sleep [105 vs. 69 minutes, P = 0.02], and a lower consolidation of daily inactivity [0.65 vs. 0.79, P = 0.03]). Conclusions: Subjective insomnia, a nonstigmatized symptom, can complement suicidality screens. Longer follow-ups and larger samples are warranted to understand whether real-time sleep monitoring predicts suicidal ideation in patient subgroups or individually.